The value of teaching increases with tool complexity in cumulative cultural evolution. Issue 1939 (18th November 2020) - Lucas, Amanda J.; Kings, Michael; Whittle, Devi; Davey, Emma; Happé, Francesca; Caldwell, Christine A.; Thornton, Alex
Abstract : Human cumulative cultural evolution (CCE) is recognized as a powerful ecological and evolutionary force, but its origins are poorly understood. The long-standing view that CCE requires specialized social learning processes such as teaching has recently come under question, and cannot explain why such processes evolved in the first place. An alternative, but largely untested, hypothesis is that these processes gradually coevolved with an increasing reliance on complex tools. To address this, we used large-scale transmission chain experiments (624 participants), to examine the role of different learning processes in generating cumulative improvements in two tool types of differing complexity. Both tool types increased in efficacy across experimental generations, but teaching only provided an advantage for the more complex tools. Moreover, while the simple tools tended to converge on a common design, the more complex tools maintained a diversity of designs. These findings indicate that the emergence of cumulative culture is not strictly dependent on, but may generate selection for, teaching. As reliance on increasingly complex tools grew, so too would selection for teaching, facilitating the increasingly open-ended evolution of cultural artefacts.